NARASI KAUMAN: STUDI PERBANDINGAN PERUBAHAN SOSIAL KAUMAN SURAKARTA DENGAN YOGYAKARTA - Fitri Damayanti; Akhmad Ramdhon (Journal of Development and Social Change, 2018)
Abstract : Kauman Surakarta become important in Surakarta in historical aspect as well as the current situation. Because the leading village Bappeda in city tourism. Kauman Yogyakarta itself is also a city government to develop tourism. However, Kauman region is not developed into a tourism, he remains intact into the territory of the strong will be the value of religious aspects although this is the influence of the community organization Muhammadiyah carried by Ahmad Dahlan. But a set of Abdi Dalem Pamethakan in Yogyakarta still exists and is still closely related to the Sultan Palace. So, compared with Yogyakarta can describe how the policy of the government of the city and claims against the city itself make Kauman Village experience social change, economic and religious. The purpose of this research is to know the changes what happened from there can be done comparatively changes and process. Next, knowing the cause/ factors changes can be analyzed the relationship Kauman Village with the life of the City of Surakarta and Yogyakarta. This research uses a type of qualitative research with ethnographic methods. How people organise their culture in their minds and then use the culture in life. In the process, changes covers 3 aspects: religious kinship, the nexus of Social Status Abdi Dalem Pamethakan that finally become economic change and the Nexus of blood that finally become social change Kauman community. From these changes are classified into 4 phases and the known causes of factors changes, namely internal factors (economy needs to change and how to maintain the existence of the village) and external factors (Tourism Policy of Local Government and the state of the Keraton Surakarta and Yogyakarta). Next, internal factors called to the village and external city. In the City of Surakarta and Yogyakarta itself together to develop tourism as a regional income. So that makes reference symbols found in the village can be an alternative tour package for the city itself. So from there can be described how the flow of a city and the village of mutual influence and also how komparasinya between the City of Surakarta and Yogyakarta City.Keyword : Social Change, Kauman, tourism, symbolsKauman Surakarta menjadi kampung unggulan Bappeda dalam pariwisata kota. Kauman Yogyakarta sendiri juga merupakan pemerintah kota yang mengembangkan pariwisata namun ia tidak berkembang menjadi pariwisata. Sehingga, membandingkannya dengan Yogyakarta dapat menerangkan bagaimana kebijakan pemerintah kota dan tuntutan terhadap kota itu sendiri membuat Kampung Kauman mengalami perubahan sosial, ekonomi dan keagamaan. Tujuan dari penelitian ini adalah mengetahui perubahan apa saja yang terjadi dari sana dapat dilakukan komparasi perubahan serta prosesnya. Selanjutnya, mengetahui penyebab/ faktor perubahan dapat dianalisis hubungan Kampung Kauman dengan kehidupan Kota Surakarta maupun Yogyakarta. Penelitian ini menggunakan jenis penelitian kualitatif dengan metode etnografi. Teknik pengambilan sampel yang digunakan adalah Purposive Sampling dan Snowball. Dalam prosesnya, perubahan sosial yang terjadi meliputi 3 aspek yaitu Pertalian Keagamaan, Pertalian Status Sosial Abdi Dalem Pamethakan yang akhirnya menjadi perubahan ekonomi dan Pertalian Darah yang akhirnya menjadi perubahan sosial masyarakat Kauman. Sedangkan perubahan status sosial abdi dalem Pamethakan adalah jumlah pengangkatan Tafsir Anom. Lalu, feedback yang diterima Penghulu Tafsir Anom. Jika jaman dahulu mendapat tempat tinggal dan uang bulanan, kini Kraton tidak memberikan upah apapun kepada Penghulu Tafsir Anom. Selanjutnya proses pertalian darah yang berawal dari perkawinan endogami namun kini sudah tidak demikian lagi dan berubah menjadi bagaimana kehidupan sosial di Kauman terbentuk. Dari perubahan tadi digolongkan menjadi 4 fase dan diketahui penyebab/faktor perubahan, yaitu faktor internal (Kebutuhan Ekonomi Berubah dan bagaimana Mempertahankan Eksistensi Kampung) dan faktor eksternal (Kebijakan Pariwisata Pemda dan keadaan Keraton Surakarta maupun Yogyakarta). Selanjutnya, faktor internal disebut dengan kampung dan eksternal kota. Di Kota Surakarta maupun Yogyakarta sendiri sama-sama mengembangkan pariwisata sebagai pemasukan daerah. Sehingga membuat rujukan simbol-simbol yang terdapat di kampung dapat menjadi alternatif paket wisata bagi kota itu sendiri. Sehingga dari sana dapat digambarkan alur bagaimana suatu kota dan kampung saling mempengaruhi dan juga bagaimana komparasinya antara Kota Surakarta dengan Kota Yogyakarta. Kata Kunci: Perubahan Sosial, Kauman, Pariwisata, Simbol